Solvent-free benzylic oxidation of aromatics over Cu(ii)-containing propylsalicylaldimine anchored on the surface of mesoporous silica catalysts. Issue 42 (6th October 2021) - Selvaraj, Manickam; Assiri, Mohammed A.; Rokhum, Samuel Lalthazuala; Manjunatha, C.; Appaturi, Jimmy Nelson; Murugesan, Sepperumal; Bhaumik, Asim; Subrahmanyam, Ch.
Abstract : A highly active mesoporous catalyst W-CPSA-SBA-15(0.2) shows unprecedented catalytic activity for the selective synthesis of aromatic ketones with 99–100% selectivity, among other CPSA functionalized mesoporous catalysts. Abstract : A sustainable method was used to produce aromatic ketones by the solvent-free benzylic oxidation of aromatics over mesoporous Cu(ii )-containing propylsalicylaldimine anchored on the surface of Santa Barbara Amorphous type material-15 (CPSA-SBA-15) catalysts. For comparison, mesoporous Cu(ii )-containing propylsalicylaldimine anchored with Mobil Composition of Matter-41 (CPSA-MCM-41) was assessed for these reactions under similar reaction conditions. The washed CPSA-SBA-15(0.2) (W-CPSA-SBA-15(0.2)) catalyst was prepared using an easy chemical method for the complete removal of non-framework CuO nanoparticle species on the surface of pristine CPSA-SBA-15(0.2) (p-CPSA-SBA-15(0.2) prepared with 0.2 wt% of Cu, and its catalytic activity was evaluated with different reaction parameters, oxidants and solvents. In order to confirm the catalytic stability, the recyclability was assessed, and the performance of hot-filtration experiments was also evaluated. All the catalysts used for these catalytic reactions were characterized using many instrumental techniques to pinpoint the mesoporous nature and active sites of the catalysts. The proposed reaction mechanism has been well documented on the basis of catalytic results obtained for solvent-free oxidation of aromatics. Based on the catalytic results, we found that W-CPSA-SBA-15(0.2) is a very ecofriendly catalyst with exceptional catalytic activity.